2020
DOI: 10.3389/fonc.2020.00390
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hyperbaric Oxygen Therapy on Pelvic Radiation Induced Gastrointestinal Complications (Rectal Bleeding, Diarrhea, and Pain): A Meta-Analysis

Abstract: Background: Radiotherapy is a routine treatment for pelvic cancer patients. While it had been proven effective, gastrointestinal side effects remain a concern, impairing the quality of life. A few studies focused on the effects of hyperbaric oxygen (HBO) treatment to alleviate radiation-induced gastrointestinal complications. This meta-analysis aimed to critically review and summarize existing literature, assessing the effectiveness of HBO therapy for the treatment of radiation-induced gastrointestinal side ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…13 HBO is effective, but use is often limited by issues of access and cost. 14 Surgery is usually reserved for patients with highly significant and debilitating bleeding, stricture, or fistula (see below) due to very high morbidity and mortality rates. 11 The ideal surgical approach, in particular the question of simple diversion versus formal resection, remains unclear.…”
Section: Proctitismentioning
confidence: 99%
“…13 HBO is effective, but use is often limited by issues of access and cost. 14 Surgery is usually reserved for patients with highly significant and debilitating bleeding, stricture, or fistula (see below) due to very high morbidity and mortality rates. 11 The ideal surgical approach, in particular the question of simple diversion versus formal resection, remains unclear.…”
Section: Proctitismentioning
confidence: 99%
“…Hyperbaric oxygen therapy (HBOT) is a further medical option for management of rectal bleeding. It is purported to act through increased stimulation of damaged cells and improves the activity of free radicals[ 49 ]. Recommendation for the use of HBOT is based on data from a 2008 double blind crossover trial carried out by Clarke et al [ 50 ].…”
Section: Rectummentioning
confidence: 99%
“…A recent combined prospective and retrospective observational trial of 52 patients who had been treated with radiotherapy for cancers of the bowel, bladder, cervix, prostate and vulva found that hyperbaric oxygen therapy can be an effective and safe treatment for pelvic late tissue radiation injury [67]. Similarly, a systematic review [68] has summarised the efficacy of hyperbaric oxygen in the management of radiation-induced bleeding, diarrhoea and pain. These data, which included only one prospective study and two randomised controlled trials, are encouraging, but they lack consistency in scoring of symptoms and response criteria.…”
Section: Hyperbaric Oxygenmentioning
confidence: 99%